Use of stromal vascular fraction stem cell therapy for functional and cosmetic outcomes in a young female patient with deep dermal flame burns on the face - Ahmet Çınar Yastı; Ali Emre Akgün; Merve Akın (Elsevier, 2022)
Second-degree dermal burns are the most distressing injuries for burn surgeons as the decision of how to approach wound closure is challenging in these burns of unknown healing potential due to the decreased keratinocyte cell and collagen reserve. Uncomplicated recovery is even more important in facial burn injuries considering the cosmetic and functional functions of the face. In this paper, we describe a patient who experienced flame burns following flash exposure and discuss the outcomes of stem cell therapy in light of the literature.Collagen-containing closure was performed by applying adipose-derived stromal vascular fraction injections below the burned areas, primarily in functionally important regions. Cosmetic and functional improvement in the burn areas covered with epidermis-like material was determined to be satisfactory both for the patient and the clinician.Based on our clinical experience, literature findings, and current case, stromal vascular fraction therapy presents as a viable option in patients with deep second-degree burns.